2006
DOI: 10.1523/jneurosci.5467-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitinase ABC Digestion of the Perineuronal Net Promotes Functional Collateral Sprouting in the Cuneate Nucleus after Cervical Spinal Cord Injury

Abstract: Upregulation of extracellular chondroitin sulfate proteoglycans (CSPGs) after CNS injuries contributes to the impediment of functional recovery by restricting both axonal regeneration and synaptic plasticity. In the present study, the effect of degrading CSPGs with the application of the bacterial enzyme chondroitinase ABC (chABC) into the cuneate nucleus of rats partially denervated of forepaw dorsal column axons was examined. A dorsal column transection between the C6 -C7 dorsal root entry zones was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
237
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(257 citation statements)
references
References 55 publications
(84 reference statements)
14
237
1
Order By: Relevance
“…Additionally, collateral sprouting of intact axons has been observed. We found that chABC injections at the brainstem after cervical spinal cord dorsal quadrant lesions promoted collateral sprouting of forepaw primary afferents remaining in the target cuneate nuclei [77]. Moreover, receptive field mapping showed that this sprouting led to more cuneate nuclei neurons responding physiologically to forepaw digits tactile stimulation.…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 77%
“…Additionally, collateral sprouting of intact axons has been observed. We found that chABC injections at the brainstem after cervical spinal cord dorsal quadrant lesions promoted collateral sprouting of forepaw primary afferents remaining in the target cuneate nuclei [77]. Moreover, receptive field mapping showed that this sprouting led to more cuneate nuclei neurons responding physiologically to forepaw digits tactile stimulation.…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 77%
“…Evidence suggests that CSPGs are up-regulated within PNNs both near and far from a CNS lesion (Massey et al, 2006). Enzymatic digestion of PNNs by chondroitinase ABC leads to reactivation of plasticity in adult animals (Corvetti and Rossi, 2005;Pizzorusso et al, 2002), and enhances spared fiber collateral sprouting and synapse formation in injured animals (Tropea et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…They are typically enhanced in regions of BBB breakdown (Fitch and Silver, 1997a;Rhodes, et al, 2006), but new evidence also suggests they are upregulated in the perineuronal net in areas distant from the lesion in synaptic centers denervated by the injury (Massey, et al, 2006). In order to appropriately manipulate the extracellular matrix, we must first consider those triggers that initiate the increased production of inhibitory molecules.…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…While the specific triggers remain unclear, there are a number of hypotheses about factors that contribute to astrocyte activation and gliosis. Degeneration of severed axon tracts appears to lead to gliosis, even in regions remote from the site of trauma in the brain or spinal cord (Barrett et al, 1981;Fitch and Silver, 1997a;Massey, et al, 2006;Murray et al, 1990;Steward and Trimmer, 1997). Cytokines or other molecules that may trigger gliosis include TNF-alpha (Rostworowski et al, 1997), endothelin-1 (Hama et al, 1997), IL-1 (Giulian and Lachman, 1985), IL-6 (Chiang et al, 1994), thrombin (Nishino et al, 1993), and CNTF (Kahn et al, 1995).…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation